A cellulosic fibre foam as a bicycle helmet impact liner for brain injury mitigation in oblique impacts - Florian Feist; Markus Wagner; Georg Baumann; Stefan Spirk; Veronika Biegler; Qixiang Jiang; Tiina Nypelö (Heliyon)
Bulky cellulosic network structures (BRC) with densities between 60 and 130 g/l were investigated as a sustainable alternative to fossil-based foams for impact liners in bicycle helmets. The mechanical properties of BRC foams were characterized across a wide range of strain rates and incorporated into a validated finite element model of a hardshell helmet. Virtual impact tests simulating both consumer information and certification scenarios were conducted to compare BRC-lined helmets against conventional expanded polystyrene (EPS) designs. Results showed that BRC outperformed EPS in oblique impacts, reducing angular accelerations and velocity changes by approximately 33 %, particularly for z-axis rotations. The average risk of sustaining AIS2 injuries and concussions was lower for BRC (8 % and 34 % respectively) compared to EPS (13 % and 46 %). However, BRC helmets exhibited bottoming out in certain straight impacts, potentially failing certification tests. This limitation was addressed through design modifications. The study demonstrates that cellulosic fibre network structures have the potential to replace fossil-based foams in bicycle helmets while providing adequate protection and improved performance in mitigating rotational forces.